Shalat: Niat, Membaca Surah Al-Fatihah menurut 4 Imam Mazhab - Samarotul Silmi; Safira Laila Wulandari; Bagus Jordan; Ikhwan Maulana; Saipuddin Yuliar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to comprehensively examine the concept of intention and the recitation of Surah Al-Fatihah in prayer from the perspective of the four imams of the schools of jurisprudence: Hanafi, Maliki, Shafi’i, and Hanbali. The background of this study is based on the existence of differing opinions among scholars, which often cause confusion among the public regarding the correct practice of prayer. The method used is qualitative research in the form of a literature review (library research), through data collection from classical fiqh texts, scientific journals, and other relevant literature. The data analysis technique employs a descriptive-comparative approach to identify the similarities and differences in the views of each school of thought. The results of the study indicate that all schools of thought agree that intention is an act of the heart that constitutes a valid condition for prayer, yet they differ regarding the timing of its performance and its verbalization. Regarding the recitation of Surah Al-Fatihah, the Shafi’i school mandates it as a pillar in every rak’ah, whereas the Hanafi school does not consider it a pillar. The Maliki and Hanbali schools adopt a moderate stance by granting leniency under certain conditions. These differences reflect the richness of Islamic jurisprudence, which is dynamic and flexible. This study is expected to provide a more comprehensive understanding and foster an attitude of tolerance in addressing differences in worship practices.